2020
DOI: 10.1001/jamaophthalmol.2019.5628
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of Intravitreal Ranibizumab With Verteporfin Photodynamic Therapy Compared With Ranibizumab Monotherapy for Patients With Polypoidal Choroidal Vasculopathy

Abstract: trial showed that for patients with polypoidal choroidal vasculopathy (PCV), intravitreal ranibizumab in combination with verteporfin photodynamic therapy improves visual acuity relative to ranibizumab monotherapy. However, whether combination therapy is incrementally cost-effective relative to monotherapy during a lifetime is unclear.OBJECTIVE To assess the incremental cost-effectiveness of combination therapy compared with ranibizumab monotherapy in patients with PCV. DESIGN, SETTING, AND PARTICIPANTSThis mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…Doble et al have shown that combination therapy (PDT + Intravitreal Ranibizumab) is more effective and less costly than Ranibizumab monotherapy during a lifetime horizon. [ 17 ] However, if the time horizon was reduced to less than 10 years and/or reduction in cost of monotherapy was done, then combination therapy was no longer cost-effective.…”
Section: Discussionmentioning
confidence: 99%
“…Doble et al have shown that combination therapy (PDT + Intravitreal Ranibizumab) is more effective and less costly than Ranibizumab monotherapy during a lifetime horizon. [ 17 ] However, if the time horizon was reduced to less than 10 years and/or reduction in cost of monotherapy was done, then combination therapy was no longer cost-effective.…”
Section: Discussionmentioning
confidence: 99%
“… 9–11 Despite economic evaluations have played a crucial role in decision-making on the value for money of high-cost medications, there was a few economic evaluations determining the cost-utility of the PCV treatments. 17 , 22 , 23 This study is the first CUA of PCV treatments conducted in Thailand under both societal and payer perspectives over the lifetime horizon. We employed two-year clinical and resources used data from the two landmark RCTs, the EVEREST II 9 , 10 and PLANET 18 , 19 studies.…”
Section: Discussionmentioning
confidence: 99%
“…Doble et al assessed the incremental cost-effectiveness of combination therapy compared with ranibizumab monotherapy. They found that combination therapy had similar costs but was slightly more effective than ranibizumab monotherapy over a lifetime [38].…”
Section: Discussionmentioning
confidence: 99%
“…To date, there is no firm evidence addressing whether performing PDT during anti-VEGF therapy is cost-effective. However, considering the superior cost-effectiveness of combination therapy demonstrated in previous studies [8,9,38], it is possible that the number of anti-VEGF injections can be reduced by administering combination therapy after the first lesion reactivation. Further studies are required to verify this.…”
Section: Discussionmentioning
confidence: 99%